The Lacanian Concept of Paranoia: An Historical Perspective - Lepoutre, Thomas; Madeira, Manoel L.; Guerin, Nicolas (Frontiers in Psychology, 2017)
This article seeks to reopen a major question raised by the Lacanian nosology of the psychoses, by looking closely at Lacan’s formulations of what he never ceased referring to as “paranoia.” While almost all classification systems of modern psychiatry, such as the ICD-10 and the DSM-5, have abandoned the specific category of paranoia, Lacan always viewed paranoia as a major category of “functional psychosis.” He held that paranoia was a qualitatively different disorder than schizophrenia, and considered it to be the principal or exemplary form of psychosis. Furthermore, in the middle period of his work, Lacan thought of paranoia in much broader terms than those of the definition proposed by Kraepelin, which he revisited, point by point, developing his theory of Freud’s concept of “Verwerfung” or foreclosure; the latter became the focal diagnostic criterion in his nosographic construction. Lacan’s privileging of and evolving theoretical views on paranoia provide a structural approach to what he called the “resistant nucleus” of psychosis; his work serves as a counterpoint to the more descriptive neo-Kraepelinian approach of contemporary psychiatric nosology.